1994
DOI: 10.1042/bj3020759
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the 5′ region of the rat ATP citrate lyase gene

Abstract: A genomic clone, encompassing the 5' flanking region and the first seven exons of rat ATP citrate lyase gene, was isolated from a rat genomic library and sequenced. Primer-extension analysis showed that mRNA is transcribed at 4407 nucleotides upstream from the translation start site. Primer-extension analysis and sequencing of ATP citrate lyase cDNA amplified by PCR showed that the promoter used for transcription is identical in mammary gland, lung, liver, brain and kidney. Southern-blot analysis showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is an SRE-like sequence (TCAGGCTAG) accompanied by an NF-Y site. Mouse ACL promoter (300 bp), that contains the same SREBP binding site and a region responsible for insulin and polyunsaturated fatty acid effects, was fused to the luciferase reporter gene (ACL-Luc) (32,47) (Fig. 2).…”
Section: Acl Gene Promotermentioning
confidence: 99%
“…It is an SRE-like sequence (TCAGGCTAG) accompanied by an NF-Y site. Mouse ACL promoter (300 bp), that contains the same SREBP binding site and a region responsible for insulin and polyunsaturated fatty acid effects, was fused to the luciferase reporter gene (ACL-Luc) (32,47) (Fig. 2).…”
Section: Acl Gene Promotermentioning
confidence: 99%
“…waxes, isoprenoids, and flavonoids in plants, sterols, and fatty acids in vertebrates), but the exact biosynthetic pathways and their regulation are not yet fully understood (Fatland et al, 2000). Green plants, a glaucophyte, fungi, and a photosynthetic prokaryote have been found to have heteromeric ACL complexes consisting of a-and b-subunits of approximately 400 and 600 amino acids in length, respectively (Nowrousian et al, 2000;Fatland et al, 2002), whereas animals have a single subunit of up to 1,100 amino acids forming homomeric complexes (Kim et al, 1994). It was therefore concluded that, in the ancestral eukaryote, the ACL complex likely consisted of two different subunits that fused into a single gene early in the animal lineage (Fatland et al, 2002).…”
Section: Comparison Of the P Tricornutum Nonredundant Set With Othermentioning
confidence: 99%
“…Recently, the 5' flanking regions of ACL gene in human has been cloned (Park et al, 1997). The sequences in the promoter of this gene is highly conserved between human and rat (Kim et al ., 1994), even though there is no homology in regions of the 5' UTR and first intron, suggesting that the regulation at transcription level takes place in the same manners in these two species. Clinically, ACL is thought to be a potential target for hypolipidemic intervention, because the specific inhibition of this enzyme in rats significantly decreased the plasma levels of cholesterol and triacylglycerol (Pearce, et al , 1998).…”
Section: Introductionmentioning
confidence: 99%